Anesthetic Implications of a Patient With Kniest Dysplasia and Mitochondrial Disease: A Case Report. Issue 8 (15th April 2019) - Salik, Irim; Kubal, Keshar; Barst, Samuel
Abstract : Kniest dysplasia, or metatropic dysplasia type II, is a rare chondrodysplasia caused by abnormal type II collagen. Clinically, it is characterized by dwarfism, deafness, skeletal derangements, and ocular abnormalities. Mitochondrial diseases produce a spectrum of abnormalities in affected individuals and predominantly impact organs of high energy utilization, including the brain, skeletal muscles, kidneys, and liver. We present the case of a 6-year-old boy with both Kniest dysplasia and underlying mitochondrial disease for examination under anesthesia before cataract surgery. Successful anesthetic management of a patient with Kniest dysplasia and a mitochondrial myopathy is discussed.